THE MODERATING ROLE OF WORK CULTURE ON THE RELATIONSHIP BETWEEN FINANCIAL INCENTIVES, ENVIRONMENTAL FACTORS, GOAL INTERNALIZATION, INTERNAL SELF-CONCEPT, AND ORGANISATIONAL POLICIES WITH EMPLOYEE MOTIVATION: EVIDENCE FROM MALAYSIA - Zaherawati Zakaria; Ahmad Fauzie Sahar; Nazni Noordin; Nurul Amira Azmi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study investigates the moderating role of work culture in the relationship between financial incentives, environmental factors, goal internalization, internal self-concept, organizational policies, and employee motivation in the Malaysian public sector, with a specific emphasis on the Social Security Organization (SOCSO) in Penang. This study uses a quantitative cross-sectional survey approach to collect data from all employees in Penang SOCSO, with purposive sampling to provide insights into the elements that drive motivation. The results show that financial incentives, internal self-concept, goal internalization, work environment, and organizational policies all have significant relationships with employee motivation. Notably, work culture was found to moderate this correlation, highlighting the importance of a supportive and collaborative environment in enhancing employee engagement. These findings are consistent with Self-Determination Theory (SDT), which emphasizes the role of autonomy, competence, and relatedness in promoting intrinsic motivation. Financial rewards, internal self-concept, and goal appreciation are key extrinsic and intrinsic motivators. A healthy work environment with effective communication and collaboration, as well as organizational rules that promote work-life balance and skill development, are also important. The study suggests that employee motivation is influenced by both internal and external influences, implying that organizations should create an environment that promotes intrinsic motivation while providing competitive financial incentives. Future research should broaden its scope to include other variables and situations, yielding more comprehensive knowledge of employee motivation across a variety of conditions.